Hubungan Kepatuhan Penggunaan Alat Pelindung Diri dengan Keluhan Dermatitis Kontak Tangan Pekerja Finishing Pabrik Kertas X Serang 2025 - Kurniawan, Diana Rotua Puspita Ekasari; Hudyono, Johannes; Winata, Susanty Dewi (Jurnal MedScientiae, 2025)
Contact dermatitis is a skin disorder resulting from direct exposure to irritants or allergens in the workplace. This study aims to determine the relationship between compliance with personal protective equipment (PPE) use and hand contact dermatitis complaints among finishing workers at Paper Factory X, Serang. The study also explores the prevalence of contact dermatitis, PPE compliance levels, and the distribution of worker characteristics. This study used quantitative analytic, a cross-sectional design and was conducted from January to March 2025, involving 88 purposively selected respondents. Data were obtained through questionnaires and medical examinations, then analyzed using the Chi-Square and Fisher’s Exact tests. The prevalence of hand contact dermatitis complaints was 7.8%, mainly found among workers over 30 years old (78.9%), with more than 5 years of service (83.3%), and contact duration of ≤8 hours (94.4%). Statistical analysis showed a significant relationship between contact duration and PPE compliance with dermatitis complaints (p-value 0,000), while age and work duration showed no significant association. It is recommended to improve routine OHS education, ensure the availability of proper PPE, and evaluate existing safety programs to enhance worker protection